Factors associated with the use of physical restraint in intensive care patients - Luana Rosas Zulian; Satomi Mori; Eliana Cavalari Teraoka; Vanessa Yukie Kita Miyasaki; Suely Sueko Viski Zanei; Iveth Yamaguchi Whitaker (SciELO, 2020)
Abstract Objective: To verify the frequency of physical restraint in patients and the factors associated with its use in the intensive care unit. Method: An observational and prospective study on the use of restraint in patients observed over two days, considering the variables: age and gender, personal and clinical characteristics, devices, adverse event and restraint use. The frequency was verified in three groups of patients with different conditions by applying the Chi-Squared, Likelihood Ratio or Kruskal-Wallis tests. The association of the variables was verified with the Multinomial Logistic Regression. Results: Eighty-four (84) patients participated. Restraint was observed in 77.4% of the 84 analyzed patients, and was more frequent in the presence of sedation, agitation and invasive devices. The chance of being restrained was at least five times higher in sedation conditions, whether in weaning or daily awakening, mechanical ventilation weaning, agitation or the presence of invasive devices. Conclusion: Restraint use was high and was associated with female gender, sedation, agitation and invasive airway. It is emphasized and important to apply policies to reduce restraint use in intensive care.